Pengaruh Lama Waktu Pengadukan Dengan Penambahan Asam Asetat Dalam Pembuatan Virgin Coconut Oil (VCO): The Effect of Stirring Time With the Addition of Acetic Acid in The Production of Virgin Coconut Oil (VCO) - Fahmi, Putri Mariska; Maryanti, Maryanti; Delvitasari, Febrina; Rini Hartari , Widia; Cerly Pramuditha, Anjeli; Kusuma, Jakty (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Virgin Coconut Oil (VCO) is unheated coconut oil processing, which leaves the oil's composition and properties unchanged. In the process of making VCO, various methods can be used, including: Techniques such as acidification, controlled heating,centrifugation, fishing, fermentation, and enzymatic. In this study, VCO was made using the acidification method with the addition of 20% acetic acid. The approach taken was a Randomized Block Design (RAK) with 2 factors and every treatmentwas carried out three times, in order for 18 experimental units to be acquired. DA variance analysis was used to examine the data and continued with BNT at a level of 5%. This study was conducted to determine the effect of the addition of acetic acid (1% and 2%) and the duration of stirring using a hand mixer with a maximum speed of 1,500 rpm for (10 minutes, 15 minutes, 20 minutes) and the interaction between the addition of acetic acid and the duration of stirring on the yield and quality produced. The VCO analysis test in this study included the yield test (%), water content (%), Free Fatty Acid (FFA) content, peroxide number, specific gravity, and organoleptic (color, aroma, taste). According to the study's findings, the highest yield was 26.84% with the addition of 1% acetic acid with a stirring time of 15 minutes.